Formation and O2/CO2 combustion characteristics of real-environment coal char in high-temperature oxy-fuel conditions. Issue 6 (December 2019) - Feng, Dongdong; Guo, Dawei; Zhao, Yijun; Tan, Heping; Chang, Guozhang; Zhang, Tianpeng; Sun, Shaozeng
Abstract: Oxygen-fuel combustion is a promising technology for CO2 emission reduction. The high-temperature entrained flow reactor and high-temperature drop tube furnace were used to analyses the formation and O2 /CO2 combustion characteristics of real-environment coal char in high-temperature oxy-fuel conditions. It proposed "inflection point standard" of high-temperature flame method for the preparation of real-environmental oxy-fuel coal char according to the flame method. The results show that the ratios of C=O/C-O and C=O/Car increase in the coal char compared with the raw coals. The trend of C=O/Car in oxy-fuel condition is opposite to that in the inert atmosphere, due to the effect of high-concentration CO2 . To achieve the burnout rate similar to air combustion for coal char, with the increase of coal rank, the O2 concentration should be enhanced. The optimal O2 concentration for the oxy-fuel combustion of JC anthracite is 30%, while that of other low-rank coals could be lower than 30%. The combustion characteristic of JC anthracite is with the highest sensitivity to temperature and O2 concentration. Graphical abstract: Image 1 Highlights: "Inflection point standard" is for preparation of real-environmental oxygen-fuel coal char. Trend of C=O/Car in oxy-fuel condition is opposite to that in inert environment. Optimal O2 concentration of JC anthracite is 30%, while that of low-rank coal is <30%.